2021
DOI: 10.3389/fped.2021.604899
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age-Specific Complete Blood Count Signatures in Necrotizing Enterocolitis

Abstract: Objective: Necrotizing enterocolitis (NEC) is characterized by peripheral cell abnormalities, yet few studies have analyzed the complete blood count (CBC) specifically by gestational age (GA). Our objective was to describe GA-specific immune abnormalities in NEC through a comprehensive analysis of the CBC differential.Methods: Using a cohort of 246 infants (177 cases, 69 controls) admitted to neonatal intensive care units at a single institution, we retrospectively analyzed CBCs around illness onset in NEC cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Grag et al have previously demonstrated that children with fulminant NEC are more prone to neutropenia and thrombocytopenia ( 16 ). Julia et al have demonstrated that surgical NEC ≥33 weeks had a percent drop in neutrophils at diagnosis of NEC ( 17 ). Experimental studies have also suggested that neutrophils are equally important in NEC as in acute intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Grag et al have previously demonstrated that children with fulminant NEC are more prone to neutropenia and thrombocytopenia ( 16 ). Julia et al have demonstrated that surgical NEC ≥33 weeks had a percent drop in neutrophils at diagnosis of NEC ( 17 ). Experimental studies have also suggested that neutrophils are equally important in NEC as in acute intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, let n = 20 and filp = 5, where n denotes the number of features in Refsol. If the index of features are 0 to 19, feature subsets f 0 , f 1 , f 2 , f 3 and f 4 are obtained by flipping the following bits, as shown in Fig 4: (0,5,10,15), (1,6,11,16), (2,7,12,17), (3,8,13,18) and (4,9,14,19). In the second strategy, the k-th subset of features is obtained by flipping n/flip contiguous bits starting from the k-th bit.…”
Section: Plos Onementioning
confidence: 99%
“…In the second strategy, the k-th subset of features is obtained by flipping n/flip contiguous bits starting from the k-th bit. Following the previous example, the feature subsets f 0 , f 1 , f 2 , f 3 and f 4 are obtained by flipping the following bits: (0,1,2,3), (4,5,6,7), (8,9,10,11), (12,13,14,15) and (16,17,18,19). With the above two searching strategies, we determine the search area for each bee.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…G-CSF has been studied as a potential therapy for infants with neutropenia and sepsis. Neutropenia may be a risk factor for the development of NEC and has been associated with worsened prognosis [104,105]. Using G-CSF to prevent or improve neutropenia could in theory offer some protection from the development of NEC.…”
Section: Granulocyte Colony Stimulating Growth Factor (G-csf)mentioning
confidence: 99%